2008
DOI: 10.1021/jm800695k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification and Biological Evaluation of New Semisynthetic Derivatives of 28,29-Didehydronystatin A1 (S44HP), a Genetically Engineered Antifungal Polyene Macrolide Antibiotic

Abstract: Twenty-three new derivatives of the heptaene nystatin analogue 28,29-didehydronystatin A(1) (1) (S44HP) were obtained by chemical modification of C16 carboxyl and amino groups of mycosamine. These derivatives comprised 15 carboxamides, 4 N-alkyl derivatives, 3 N-derivatives containing additional N-linked monosaccharide or disaccharide moiety (products of Amadori rearrangement), and 1 N-aminoacyl derivative. The derivatives have been tested in vitro against yeasts Candida albicans, Cryptococcus humicolus, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…8 The in vitro antifungal activities of DMAP-amide against four tested fungal strains were comparable with those of AmB and 1, but the in vivo studies clearly showed superior pharmacological properties of this derivative over AmB. 8 The marked antifungal activity shown by a number of 28,29-didehydronystatin A 1 derivatives and particularly by the DMAPamide of 28,29-didehydronystatin A 1 (3) promoted a further structural modification study in our laboratory. On the basis of previously obtained structure-activity relationships, we designed and synthesized derivatives of 1, substituted both at the carboxyl and amino groups, and studied their antifungal activity.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…8 The in vitro antifungal activities of DMAP-amide against four tested fungal strains were comparable with those of AmB and 1, but the in vivo studies clearly showed superior pharmacological properties of this derivative over AmB. 8 The marked antifungal activity shown by a number of 28,29-didehydronystatin A 1 derivatives and particularly by the DMAPamide of 28,29-didehydronystatin A 1 (3) promoted a further structural modification study in our laboratory. On the basis of previously obtained structure-activity relationships, we designed and synthesized derivatives of 1, substituted both at the carboxyl and amino groups, and studied their antifungal activity.…”
Section: Introductionmentioning
confidence: 88%
“…8 The corresponding N-Fmoc derivatives of amides 2-4 were purified by column chromatography and deprotected, resulting in amides 2-4 with high purity.…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations